Development of Video Based on Pop Up Questions Integrated Religious Character Human Digestive System Materials - Nurhidayah Nurhidayah; Jumaeri Jumaeri; Endang Susilaningsih (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to test the validity, practicality, and effectiveness of pop-up questions-based learning videos integrated with religious characters of the human digestive system. The subjects of this study were students of class VIII A and VIII C of MTs Mazro'illah, Lubuklinggau City. This research is a type of research and development (R&D) that uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The data collection instruments in this study consisted of interview guides, expert validation questionnaires, practicality questionnaires, and test sheets. The results of the research data analysis showed that the experts stated that the three learning videos developed were very valid with an average score of 89.70% for the first video, 91.40% for the second video, and 90.80% for the third video. The learning videos that have been declared valid are then tested on students to find out the practicality of the learning videos developed. The results of the practicality questionnaire showed good responses by students and teachers with an average score of 85 and 84, respectively. The learning videos developed were then implemented for students to determine the effectiveness in aspects of knowledge and attitudes. The test results show that the ability of the students' knowledge aspect is still in the poor category with an average score of 55.20%, while the attitude aspect of students shows different things with an average score of 92.50% which is included in the very good criteria. Based on the results of this study, the pop-up question-based learning video integrated with the religious character of the human digestive system material was declared to be very valid, practical, and effective in the aspect of religious attitudes to be used in learning